KARAKTERISTIK POKOK FILSAFAT DALAM NOVEL PANGANTÉN KARYA DEDEN ABDUL AZIZ - Herlina, Yeni; Sudaryat, Yayat (Magistra Andalusia: Jurnal Ilmu Sastra, 2024)
This research aims to explain the philosophical study and key characteristics of philosophy in the novel Pangantén by Deden Abdul Aziz. A descriptive qualitative approach was used to analyze data from novel excerpts that reflect philosophical inquiry. Data were collected through the process of reading, noting, and marking relevant quotes. The results of the research show 63 pieces of philosophical data and 5 key characteristics of philosophy. Among them, 13 data points depict radical thinking, focusing on fundamental questions about human life and existence. A total of 20 data points relate to the search for basic principles or foundations, reflecting a contemplation of values that guide human behavior. Additionally, 8 data points reflect the pursuit of truth, another 8 depict efforts to achieve conceptual clarity, and 14 data points describe rational thinking, emphasizing logic and reasoning in decision-making. These results indicate that the novel Pangantén not only presents a narrative but also conveys deep philosophical reflections. These elements position the novel as a medium for illustrating philosophical ideas about existence, principles, truth, clarity, and rationality in everyday life.